Regulatory T cells constrain the TCR repertoire of antigen‐stimulated conventional CD4 T cells. (20th December 2017) - Fontaine, Martina; Vogel, Isabel; Van Eycke, Yves‐Rémi; Galuppo, Adrien; Ajouaou, Yousra; Decaestecker, Christine; Kassiotis, George; Moser, Muriel; Leo, Oberdan
Abstract: To analyze the potential role of Tregs in controlling the TCR repertoire breadth to a non‐self‐antigen, a TCRβ transgenic mouse model (EF4.1) expressing a limited, yet polyclonal naïve T‐cell repertoire was used. The response of EF4.1 mice to an I‐Ab‐associated epitope of the F‐MuLV envelope protein is dominated by clones expressing a Vα2 gene segment, thus allowing a comprehensive analysis of the TCRα repertoire in a relatively large cohort of mice. Control and Treg‐depleted EF4.1 mice were immunized, and the extent of the Vα2‐bearing, antigen‐specific TCR repertoire was characterized by high‐throughput sequencing and spectratyping analysis. In addition to increased clonal expansion and acquisition of effector functions, Treg depletion led to the expression of a more diverse TCR repertoire comprising several private clonotypes rarely observed in control mice or in the pre‐immune repertoire. Injection of anti‐CD86 antibodies in vivo led to a strong reduction in TCR diversity, suggesting that Tregs may influence TCR repertoire diversity by modulating costimulatory molecule availability. Collectively, these studies illustrate an additional mechanism whereby Tregs control the immune response to non‐self‐antigens. Synopsis: High throughput sequencing of TCRs expressed by antigen‐stimulated CD4 T cells demonstrates that Tregs control both the magnitude and the breadth of an immune response. Treg depletion before immunization leads to enhanced antigen specific immune responses in a TCR Vβ transgenic mouse model. Analysis of TCR Vα chain expressed by antigen‐specific, conventional CD4 + T lymphocytes reveals that Treg depletion allows the emergence of a wider repertoire comprising novel, mostly private, antigen‐specific clonotypes. CD86 costimulatory blockade reduces the TCR repertoire diversity suggesting that Tregs may control the TCR repertoire by decreasing the costimulatory signals on APC. The capacity of Tregs to limit the TCR repertoire diversity may represent a mechanism to control the development of self‐reactive and/or harmful immune responses. Abstract : High‐throughput sequencing of T‐cell receptor genes from antigen‐stimulated CD4 T cells demonstrates that Tregs control both the magnitude and the breadth of an immune response.